Effect of titanium suboxides on the reaction mechanism of hydrogen-reduced ilmenite. (15th January 2023) - Yu, Han; Li, Chen; Wei, Kuixian; Li, Yang; Ma, Wenhui
Abstract: Hydrogen metallurgy, as a green metallurgical technology, is one of the effective ways to reduce carbon emissions. The generation of titanium suboxides (Tin O2n-1, 3 ≤ n ≤ 9) during the hydrogen reduction of ilmenite results in abundant hydrogen and heat loss. In this study, the ability of titanium suboxides to reduce ilmenite is systematically analyzed and confirmed. Thermodynamic calculations reveal that these titanium suboxides exist stably and reduce ilmenite when the reaction temperature exceeds 1100 K. Validation experiments indicate that Ti3 O5 can be used to reduce ilmenite to iron and rutile. Furthermore, by controlling the reduction time and holding operation in an inert atmosphere, the discovery of metallic iron particles generated inside unreacted ilmenite. This shows that titanium suboxides can reduce ilmenite, and also the metallization rate of iron is increased. This study has great guideline significance for the clean and green production of ilmenite. Highlights: The mechanism of hydrogen reduction of ilmenite is expounded. Stable existence of titanium suboxides at reaction temperatures exceed 1100 K. Titanium suboxides can reduce ilmenite is confirmed. The metallization rate can be increased by holding operation.